POTENSI DESA BAJO SEBAGAI DAYA TARIK WISATA ALAM DI KABUPATEN BOALEMO - Desrika Talib; Anggraeni M.S Lagalo (Tulisan Ilmiah Pariwisata (TULIP), 2024)
Bajo Village has beautiful natural scenery and there are exotic islands around it. This study aims to determine the potential of Bajo Village as a natural tourist attraction in Boalemo Regency through the application of tourism components (Attraction, Amenity, Accessibility and Ancillary). This research is a qualitative study with data collection techniques through observation, interviews and documentation. The results of the research are Attraction in Bajo Village in the form of beautiful natural scenery and there are several small islands and can see natural panoramas (sunset) and there are also photo spots. Amenity there are villas that can support tourist activities staying in Bajo Village, there are food stalls owned by the bajo community and mosques. Accessibility is good because there is an easy way to reach Bajo Village, this can be seen from the paved highway and there are direction boards to Bajo Village. However, the road that will be passed to Bajo Village is a little narrow. Ancillary there is an active youth organization that can support tourism activities in Bajo Village